The Effectiveness of Fulfilling Children's Educational Rights in the Legal Development Process - Anggraeni, Afifah Dhaninta; Adityo, Rayno Dwi (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study investigates the legal effectiveness of fulfilling the right to education for children in conflict with the law at the Child Special Development Institution (LPKA) Class I Blitar, Indonesia, applying Soerjono Soekanto’s framework of legal effectiveness. Using a juridical-empirical approach, data were collected through semi-structured interviews with institutional staff, analysis of official documentation, and review of relevant laws and regulations. Addressing a gap in existing scholarship, which largely centers on child victims, this research focuses on convicted juveniles as legal subjects entitled to educational rights. The findings reveal that the fulfillment of educational rights at LPKA Class I Blitar can be categorized as “quite effective,” supported by structured formal and non-formal programs, the operation of a self-managed primary school, diverse life skills training, and collaboration with 40 stakeholder institutions. Nevertheless, significant obstacles persist, including the heterogeneity of educational backgrounds among fostered children, limited adaptive learning facilities, and insufficient community engagement. These factors undermine the community and cultural dimensions of legal effectiveness, despite strong performance in legal substance, law enforcement, and facilities. Theoretically, the study validates Soekanto’s framework in the context of juvenile justice, emphasizing the interplay between legal, institutional, community, and cultural dimensions. Practically, it proposes a scalable multi-stakeholder cooperation model to enhance educational quality and sustainability in correctional settings. These findings suggest that legal effectiveness should be evaluated not only through institutional compliance but also through the extent to which education fosters genuine rehabilitation and social reintegration, aligning national practices with international child rights standards.